Science and Technology Studies in Policy: The UK Synthetic Biology Roadmap. (January 2020) - Marris, Claire; Calvert, Jane
In this paper, we reflect on our experience as science and technology studies (STS) researchers who were members of the working group that produced A Synthetic Biology Roadmap for the UK in 2012. We explore how this initiative sought to govern an uncertain future and describe how it was successfully used to mobilize public funds for synthetic biology from the UK government. We discuss our attempts to incorporate the insights and sensibilities of STS into the policy process and why we chose to use the concept of responsible research and innovation to do so. We analyze how the roadmapping process, and the final report, narrowed and transformed our contributions to the roadmap. We show how difficult it is for STS researchers to influence policy when our ideas challenge deeply entrenched pervasive assumptions, framings, and narratives about how technological innovation necessarily leads to economic progress, about public reticence as a roadblock to that progress, and about the supposed separation between science and society. We end by reflecting on the constraints under which we were operating from the outset and on the challenges for STS in policy.